2022
DOI: 10.3390/cancers14133036
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic MicroRNA Panel for HCV-Associated HCC: Integrating Computational Biology and Clinical Validation

Abstract: Early detection of hepatocellular carcinoma (HCC) will reduce morbidity and mortality rates of this widely spread disease. Dysregulation in microRNA (miRNA) expression is associated with HCC progression. The objective is to identify a panel of differentially expressed miRNAs (DE-miRNAs) to enhance HCC early prediction in hepatitis C virus (HCV) infected patients. Candidate miRNAs were selected using a bioinformatic analysis of microarray and RNA-sequencing datasets, resulting in nine DE-miRNAs (miR-142, miR-15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
3
0
2
Order By: Relevance
“…Nine miRNAs (miR-142, miR-150, miR-183, miR-199a, miR-215, miR-217, miR-224, miR-424 and miR-3607) were discovered to be differentially expressed in HCC and HCV patients compared to healthy volunteer serum specimens. The investigators combined miR-150, miR-199a, miR-224, miR-424 and miR-3607 together as an early detection instrument and it did show better sensitivity and specificity [135]. miR-497 and miR-1246 levels not only related to TNM stages and metastasis in HCC but also to some extent, could act as a prognostic predictor [118].…”
Section: Circulating Micrornamentioning
confidence: 99%
“…Nine miRNAs (miR-142, miR-150, miR-183, miR-199a, miR-215, miR-217, miR-224, miR-424 and miR-3607) were discovered to be differentially expressed in HCC and HCV patients compared to healthy volunteer serum specimens. The investigators combined miR-150, miR-199a, miR-224, miR-424 and miR-3607 together as an early detection instrument and it did show better sensitivity and specificity [135]. miR-497 and miR-1246 levels not only related to TNM stages and metastasis in HCC but also to some extent, could act as a prognostic predictor [118].…”
Section: Circulating Micrornamentioning
confidence: 99%
“…Furthermore, many miRNAs may be both up-and down-regulated in HCC patients, which could lead to analytical difficulties in clinical practice. However, a small number are reported to be upregulated in HCC patients in more than a few publications, the most common of which are miR-21 [11,15,23,[26][27][28], miR-29 [22,26,[29][30][31], miR-192 [11,15,30], miR-199 [15,31,32], miR-221 [26,33,34], miR-222 [26,34], and miR-224 [18,32,35]. Of four meta-analyses that evaluated the diagnostic value of miRNAs for HCC detection, three cautiously encouraged their role as biomarkers [27,36,37], whereas one concluded that adding miRNA to the protein biomarkers AFP or DCP did not improve the diagnostic performance [28].…”
Section: Introductionmentioning
confidence: 99%
“…О связи ВГВ с возникновением ГЦК свидетельствует и то, что у подавляющего большинства больных ГЦК (в отличие от пациентов без рака) выявляются интеграции ДНК HBV в геном гепатоцитов. Причем относительная распространенность вирусных интеграций в тканях опухоли намного выше, чем в окружающих тканях печени [7].…”
unclassified
“…При сравнении микроРНК в ВГB-и ВГC-ассоциированных ГЦК было выяснено, что при ГЦК, ассоциированной с ВГС, дифференциально дерегулируемые микроРНК связаны с регуляцией иммунного ответа, презентацией антигена, клеточным циклом или липидным метаболизмом, в то время как при ГЦК, ассоциированной с ВГВ, они скорее вовлечены в пути, регулирующие гибель клеток, повреждение ДНК или передачу сигнала [7].…”
unclassified